PERILAKU TERITORIAL PEDAGANG INFORMAL TERHADAP KESELAMATAN PEJALAN KAKI DI KOTA BALIKPAPAN - Thirafi, Tomy Aufar; Maslina, Maslina; Zainul, L.M. (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
Sidewalks are made to provide convenience for pedestrians to be able to access public roads while also protecting from the dangers of passing vehicles (accidents). But now, most of the sidewalks have changed their main function. In some corners of the city of Balikpapan, we can see a lot of sidewalks that are used by informal traders as a place to open their sales. For this reason, pedestrians must go down to the shoulder of the road to walk. The aim of the researcher to achieve this research is to find out the territorial behaviour of informal traders towards pedestrian safety. The research methodology used is a qualitative descriptive methodology with the main goal of making a picture or description of an application objectively The results showed that the impact of this behaviour on pedestrian safety in the form of defective functions of the sidewalk on the road, where there is only one side of the sidewalk that can be used because it is not used to sell. So pedestrians also try to cross to use sidewalk facilities on the other side that are not used to sell traders who have the risk of conflict between pedestrians and vehicles at the crossing point.